1997
DOI: 10.1007/pl00004977
|View full text |Cite
|
Sign up to set email alerts
|

Non-neuronal acetylcholine, a signalling molecule synthezised by surface cells of rat and man

Abstract: Acetylcholine acts as a prominent transmitter in the central and peripheral nervous system. The aim of the present study was to investigate whether mammalian non-neuronal cells can synthesize and store acetylcholine. A cotton tipped applicator (Q-tip) was used to collect surface cells from airways and alimentary tract. Histological inspection indicated that rubbing of the luminal surface of human bronchi did not penetrate the basal membrane. Acetylcholine was measured by an HPLC-method using substrate-specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
214
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(229 citation statements)
references
References 23 publications
15
214
0
Order By: Relevance
“…Kawashima and Wessler [30,31] speculated that non-neuronal and non-central cells synthesize ACh. Our recent study has demonstrated for the first time that cardiomyocytes also possess the intracellular ACh synthesis system, which is transcriptionally activated in a positive feedback manner, and donepezil also elevates ACh level in cardiomyocytes, which was partly independent of muscarinic receptors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Kawashima and Wessler [30,31] speculated that non-neuronal and non-central cells synthesize ACh. Our recent study has demonstrated for the first time that cardiomyocytes also possess the intracellular ACh synthesis system, which is transcriptionally activated in a positive feedback manner, and donepezil also elevates ACh level in cardiomyocytes, which was partly independent of muscarinic receptors [29].…”
Section: Discussionmentioning
confidence: 99%
“…ChAT was used to indicate the presence of acetylcholine, since it is essential in the synthesis of the neurotransmitter and is a specific marker of cholinergic nerves and acetylcholine-containing cells. ChAT has been identified by immunohistochemisty in the cell bodies and nerve terminals of both submucosal and myenteric plexus neurons (27); in addition, the cell membrane, endosomes, cytoskeleton, nucleus, and mitochondria of epithelial cells have also been shown to be immunoreactive (16). In our study, densitometry analysis of Western blots revealed a significant increase in the expression of ChAT relative to the expression of PGP9.5, a neuronal marker, suggesting that increased enzyme levels were present in the enteric nerves of MS pups.…”
Section: Discussionmentioning
confidence: 99%
“…The recent discovery that lung cancers synthesize and secrete acetylcholine (ACh) that acts as an autoparacrine growth factor provides potential new targets to inhibit lung cancer growth. 3,4 It is well established that ACh is an important neurotransmitter in the central and peripheral nervous systems and acts via activation of ACh receptors (AChRs).Recently, it has been found that ACh is also widely synthesized by a variety of non-neuronal cell types including airway epithelial cells, 5,6 keratinocytes, 7 small and large intestine, gall bladder, 8 glial, 9 vascular endothelial, 10 immune cells and most common cancer cells such as NSCLC, SCLC, colon, glial and ovarian carcinomas. [11][12][13][14][15][16] Although the primary function has not yet been completely elucidated, the expression of ACh in many different cell types suggests that its roles will be fundamental and will present novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%